Journals 1952 - 2000 - Schlesinger, Arthur M. 1917-2007 (Penguin Press, 2007)
The distinguished political historian's journals provide an intimate history of post-war America, the writer's contributions to multiple presidential administrations, and his relationships with numerous cultural and intellectual figures